2018
DOI: 10.21511/imfi.15(3).2018.13
|View full text |Cite
|
Sign up to set email alerts
|

Exploring frequency of price overreactions in the Ukrainian stock market

Abstract: AUTHORS Alex AbstractThis paper explores the frequency of price overreactions in the Ukrainian stock market by focusing on the PFTS Index over the period 2006-2017 and UX index over the period 2008-2017, as well as some "blue chips" (BAVL, UNAF, MSICH, CEEN) for the period of 2013-2015. Using static approach to detect overreactions, a number of hypotheses are tested: the frequency of price overreactions is informative about crisis events in the economy (H1), can be used for price prediction purposes (H2), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
4
0
2
Order By: Relevance
“…By contrast, Cox and Peterson (1994) concluded that it is doubtful that large one-day price falls provide the opportunity for a short-term profitable trading strategy based on stock market overreaction given the relatively small size of price reversals and the presence of trading costs. Abnormal price changes and overreactions can also be used as a crisis identifier and a price predictor (Sandoval and Franca, 2012; Plastun et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By contrast, Cox and Peterson (1994) concluded that it is doubtful that large one-day price falls provide the opportunity for a short-term profitable trading strategy based on stock market overreaction given the relatively small size of price reversals and the presence of trading costs. Abnormal price changes and overreactions can also be used as a crisis identifier and a price predictor (Sandoval and Franca, 2012; Plastun et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, it can be noted that researches of the interconnections that arise between Ukrainian stock indexes and world stock indices are practically absent. While choosing a basic stock index for our research, we relied on the results obtained in scientists` researches of the analysis of the status of Ukrainian stock exchanges and the behaviour of stock indices, in particular the study on the determination of the frequency of excessive price reactions, on the example of the PFTS index and the UX index (Plastun et al, 2018), which analysed a number of hypotheses about the possibility of using these indices as predictors of crisis phenomena in the economy, as well as for forecasting of profitability of shares and using a correlation analysis, regression analysis with fictitious variables, and also statistical tests (expanded Dicky-Fuller test of Granger causality test) proved that the indicated indices are informative and can be used for the development of trading strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Overreaction terjadi karena adanya return abnormal pada distribusi harga akibat adanya suatu berita, baik berita buruk maupun berita baik. Melalui pengujian secara statik dengan menggunakan 2 buah indeks dan beberapa saham blue chips, dibuktikan bahwa overrection terjadi pada pasar modal Ukraina (Plastun et al, 2018). Selain penelitian overreaction secara statik, pembuktian secara statik dan dinamik juga dilakukan untuk meneliti frekuensi harga overreaction dengan statistik parametrik dan non parametrik (Caporale & Plastun, 2019a).…”
Section: Pendahuluanunclassified
“…Reaksi pasar berlebih banyak terjadi pada pasar modal tidak efisien, khususnya pada pasar modal berkembang. Penelitian overreaction terbukti signifikan terjadi pada pasar modal berkembang dan tidak efisien, misal Santosa & Santoso, (2019), Plastun et al, (2018) Chaouachi & Douagi, (2014). Penelitian overreaction tetap menarik untuk diteliti agar dapat diperoleh hasil yang konsisten dari waktu kewaktu (robust), seperti penelitian terkini di Ukraina menghubungkan overreaction dengan struktur pasar mikro melalui momentum dan dampak contrarian (Plastun et al, 2020).…”
Section: Market Overreactionunclassified